Design and Construction of A Bunut Oven Based on Artificial Intelligence - Sulandari Sulandari; Dian Wardana; Laili Suryani; Ibnu Akbar; Akbar Hasadi Putra S; Rita Juliani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
Artificial Intelligence-based shoe oven design has been carried out to provide an even heating process for leather shoes so that the shoe bends are perfect. The process of making leather shoes is carried out in several stages, namely designing an oven using solid work software, collecting quality tools and materials, making shoe ovens, making Arduino programs and Artificial Intelligence applications using MIT App Inventor, and testing. The shoe oven has two main chambers, namely the combustion chamber and the shoe heating chamber. The shoe oven works with the help of an Artificial Intelligence application that can monitor and control the oven with a maximum distance of 5 meters through the monitoring mode and the input set setting mode. The shoe oven is set to a temperature of (50-55)oC with a heating time of (30-60) minutes and has the ability to withstand constant heat for 45 minutes to dry the leather and perfect the curve of the shoe with the help of Arduino. Artificial Intelligence-based shoe ovens can improve shoe quality in a faster and controlled time.